2022
DOI: 10.1371/journal.pone.0271905
|View full text |Cite
|
Sign up to set email alerts
|

MRN-dependent and independent pathways for recruitment of TOPBP1 to DNA double-strand breaks

Abstract: Ataxia Telangiectasia mutated and RAD3-related (ATR) kinase is activated by DNA replication stress and also by various forms of DNA damage, including DNA double-strand breaks (DSBs). Recruitment to sites of damage is insufficient for ATR activation as one of two known ATR activators, either topoisomerase II-binding protein (TOPBP1) or Ewing’s tumor-associated antigen 1, must also be present for signaling to initiate. Here, we employ our recently established DSB-mediated ATR activation in Xenopus egg extract (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…Finally, Yoo and colleagues showed that mutations in the PBPs from both TOPBP1 (BRCT1) and NBS1 (BRCT1) prevented efficient interaction. We have recently shown that MRN is important for recruitment of TOPBP1 to long, linearized dsDNA templates that mimic DSBs (Montales et al, 2022). Given these findings, we were motivated to analyze the TOPBP1-NBS1 interaction in more detail.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, Yoo and colleagues showed that mutations in the PBPs from both TOPBP1 (BRCT1) and NBS1 (BRCT1) prevented efficient interaction. We have recently shown that MRN is important for recruitment of TOPBP1 to long, linearized dsDNA templates that mimic DSBs (Montales et al, 2022). Given these findings, we were motivated to analyze the TOPBP1-NBS1 interaction in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, we expressed and purified from E. coli two GST-NBS1 1-400 fusion proteins, one corresponding to the wild type sequence and the other containing a K158E mutation that attenuates the PBP in BRCT1 of NBS1 (Figure 1A). These proteins, along with GST alone, were added to XEE in either the presence or absence of linearized 5kb dsDNA, which we have previously shown will potently activate both ATR and ATM in our XEEs (Montales et al, 2021; Ruis et al, 2022; Montales et al, 2022). The GST protein complexes were then recovered back out of the XEE using glutathione-sepharose beads, and the presence of endogenous TOPBP1 was detected via Western blotting.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The beads are then incubated in XEE containing myc-tagged forms of either wild type or S1131A TOPBP1. Since our previous work has repeatedly shown that TOPBP1 does not bind to streptavidin beads lacking DNA under these assay conditions (Montales et al, 2021; Ruis et al, 2022; Montales et al, 2022), we did not include empty beads in this experiment. After incubation, the beads were isolated, washed, and probed for TOPBP1 occupancy by Western blotting.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we use our D SB- m ediated A TR activation in X enopus egg extract system (DMAX; Montales et al, 2021; Ruis et al, 2022; Montales et al, 2022) to study how TOPBP1’s AAD is regulated. DMAX offers several powerful advantages for mechanistic studies of ATR signaling.…”
Section: Introductionmentioning
confidence: 99%